Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.22547/ber/6.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Workplace Bullying on Turnover Intention of Faculty Members: A Case of Private Sector Universities of Khyber Pakhtunkhwa, Pakistan

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Meanwhile, Van Schalkwyk, Els, and Rothmann (2011) found a positive relationship between exposure to workplace bullying strategies from supervisors and colleagues and turnover intention (r= .28 & .21, p< .01, respectively) in a convenience sample of 13, 911 employees. Razzaghian and Ghani (2014) found that workplace bullying accounts for 20.4% variation on turnover intention in a sample of 207 faculty members of different private universities. Moreover, there are some studies in which examined the long-term effects of exposure to workplace bullying on turnover intention; for example, Glambek et al (2014) conducted a longitudinal study in which they examined if exposure to workplace bullying has an effect on turnover intention and if this effect persists for a long period of time.…”
Section: Workplace Bullying Job Satisfaction Work Engagement and Bumentioning
confidence: 99%
“…Meanwhile, Van Schalkwyk, Els, and Rothmann (2011) found a positive relationship between exposure to workplace bullying strategies from supervisors and colleagues and turnover intention (r= .28 & .21, p< .01, respectively) in a convenience sample of 13, 911 employees. Razzaghian and Ghani (2014) found that workplace bullying accounts for 20.4% variation on turnover intention in a sample of 207 faculty members of different private universities. Moreover, there are some studies in which examined the long-term effects of exposure to workplace bullying on turnover intention; for example, Glambek et al (2014) conducted a longitudinal study in which they examined if exposure to workplace bullying has an effect on turnover intention and if this effect persists for a long period of time.…”
Section: Workplace Bullying Job Satisfaction Work Engagement and Bumentioning
confidence: 99%
“…In school-going adolescents of Pakistan, 41.3% (n=4676) were the victims of bullying however the prevalence of bullying in females were 35.5% 23 . In our study ( 24 . In this study, Table 2 shows the prevalence of bullying among government and private sectors educational institutes.…”
Section: Methodsmentioning
confidence: 60%
“…(Duarte & Pinto‐Gouveia, ; Duarte, Pinto‐Gouveia, & Cruz, ). Bullying behaviour can also lead to turnover and intent to leave (Blackstock, Harlos, Macleod, & Hardy, ; Hayward, Bungay, Wolff, & MacDonald, ; Malik, Sattar, Shahzad, & Faiz, ; Razzaghian & Ghani, ). While these findings linking negative characteristics to bullying are not unique to this study, they strongly support the continued need for hospital and nursing leadership to improve the work environment.…”
Section: Resultsmentioning
confidence: 99%